Atmospheric turbulence spectrum in high resolution mode detected by a high power-aperture sodium lidar over Yanqing, Beijing (40.47°N, 115.97°E). (August 2021) - Zou, Xu; Wang, Jihong; Li, Faquan; Yang, Yong; Wu, Fuju; Cheng, Xuewu; Gong, Shunsheng; Yang, Guotao
Highlights: High Power-Aperture lidar system with two wavelengths and three channels for Rayleigh scattering, Mie scattering and Na fluorescence simultaneous detecting was completed at Beijing (Yanqing District, 40.3°N, 116.2°E). The excellent detecting performance of the lidar as photon counts shows a considerable high value of which the sodium layer echo peak value can reach to more than 37000 counts. A relevant advanced lidar detecting standard has been realized. High resolution mode (15 m, 6.7 s) has been implemented while photo count per shot reaches to a considerable high value as 861, and the Power-Aperture Product can reach to 0.7 Wm 2 which is equivalent to the largest LZT lidar (6-meter diameter, 5 w power, 1500 photocount per shot, 0.6 Wm 2 at UBC, Canada), ALO (1000 photocount per shot 0.6 Wm 2 at Cerro Pachón, Chile) and STAR (Boulder, Colorado US) lidar as their high level standard at the moment. Based on this High Power-Aperture lidar, the first report of observations of turbulence spectrum in North hemisphere over China was provided, which had been extremely difficult to be observed due to the resolution and the signal/noise rate as in before for most researches. The observed turbulence spectrum was found in consistent with the only report by ALO lidar at Chile in South hemisphere observed in 2017 [Y. Guo et. al., Geophys.Res.Lett., 2017 ] and well fitted with the theory prediction, which can effectively help us to further understand the entire global gravity wave behavior. Abstract: With the support of the Meridian Project of China, an integrated two-wavelength and three-channel lidar system was completed for atmospheric detection in Yanqing, Beijing. This lidar system emitted a 589 nm laser beam for detecting the 80–110 km sodium atomic layer. A 532 nm laser system was used to detect the 30–80 km atmospheric temperature and density and also to provide the atmosphere aerosol information from the ground to a height of 30 km. Because all of the technique details were carefully designed, this lidar obtained a very good signal and achieved the full-scale detection of the atmosphere from near-ground to a height of 110 km. With the conventional mode (3 minutes, 100 m), the atmospheric 532 nm Rayleigh detecting channel could reach a height of 80 km, and the 589 nm channel photo counting peak could reach 37000. This specification actually reached the high power-aperture sodium lidar standard in advance, which caused the high-resolution detection mode (15 m, 6.7 s) to be realized. For the high-resolution detecting mode of our Yanqing Lidar, observations of the spectrum of a gravity wave in the turbulence region were given according to the advantages of the high signal/noise ratio. Additionally, the properties of the turbulence spectrum and their variations were first obtained in the northern hemisphere over China. The observed gravity wave turbulence spectra well fitted with the theoretical prediction. These results achieved new field detections, which will lead us to further discover the nature and essence of a gravity wave and deeply study the behavior of upper atmosphere circulation on a large scale.